AN ANALYSIS OF THE TYPES AND FUNCTIONS OF CODEMIXING IN THE INSTAGRAM CAPTION OF GRADE XI STUDENTS AT SMA NEGERI 14 MEDAN - Fera Thessa Yanti Simatupang; Rina Octavia Simarmata; Sahat Taruli Siahaan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to identify the types of code mixing and to determine the dominant type used in students’ Instagram captions. This research is based on the phenomenon of bilingual language use in social media, especially the combination of Indonesian and English in students’ daily communication. This research applied a descriptive qualitative method. The subjects of this research were 50 eleventhgrade students of SMA Negeri 14 Medan, selected from a population of 240 students. The data consisted of 50 Instagram captions and were supported by written interviews conducted through Instagram direct messages. The data were analyzed using the theory proposed by Pieter Muysken, which classifies code mixing into three types: insertion, alternation, and congruent lexicalization. The results of this research show that all three types of code mixing were found in the students’ captions, with alternation identified as the most dominant type. This indicates that students tend to switch between Indonesian and English within sentences or clauses. Furthermore, code mixing reflects students’ flexibility in digital communication and serves as a means of expressing identity, style, and creativity in social media.